Earthquake Simulation Design Using Virtual Reality at the East Java Province Environmental Agency Building: English - Dirama, Romeo; Rizqi Novita Sari (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study presents the development of a virtual reality-based simulation aimed at improving earthquake disaster preparedness at the East Java Provincial Environmental Service Building. The simulation introduces proper emergency response procedures, realistic earthquake scenarios, and comprehensive knowledge of building layouts, evacuation route signs, and designated assembly points. The research methodology involved direct observations and interviews with employees to gather detailed information about existing preparedness measures. The simulation was developed through stages of problem identification, data collection, object modeling using Blender 3D, and integration into a cohesive system via Unity. The final implementation resulted in a dynamic, interactive, and educational simulation that closely mirrors real-life emergency situations. Testing results indicate that the simulation operates effectively, providing immersive experiences and facilitating user interaction. This tool is expected to enhance the understanding of emergency procedures for employees, particularly new staff and visitors, while fostering a safer, disaster-prepared work environment. The study underscores the potential of virtual reality technology as a strategic approach to disaster risk reduction and education.